Screening of Natural Dyes from Selected Fungal Species: Analysis of Natural Dyes - Naz, Tasbiah; Sikandar, Shomaila; Sajjad, Fatima; Alim-un-Nisa; Afzal, Imran; Fatima, Anum; Rubab, Nayyar; Sattar, Rabia (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Some fungi are observed as effective pigments. Its importance in the production of natural pigments has grown significantly. The pigment-producing fungi were developed and evaluated for application in dyeing cotton fabric. In the research, five fungal strains were identified as Aspergillus terreus S10, Talaromyces atroroseus WW5A3, Penicillium oxalicum WW3A4 (DG), WW5C2 and WW31DG. These strains were incubated for 21 days under static and non-static conditions using MSM and PDB media. Under liquid state fermentation conditions, the production of the pigments by the fungus was improved by altering temperatures (25-35°C) and pH (4.5-6.5). T. atroroseus WW5A3 showed pinkish color, A. terrreus S10 displayed yellow color, P. oxalicum WW3A4 (DG) presented yellowgreenish, WW5C2 exhibited light yellow color and WW31DG demonstrated greenish color. The results showed the maximum percentage absorbance of T. atroroteus WW5A3 showed 90.36 % at 600 nm, A. terrreus S10 showed 88 % at 500 nm, P. oxalicum WW35A4 showed 46.04 % at 550 nm, WW5C2 showed 59.60 % at 550 nm, and WW31DG showed 81.9 % at 550 nm. The natural fungal pigments were tested against bacterial pathogens to check the antibacterial activity. The results indicated that S. aureus and E. coli exhibited antibacterial activity in terms of maximum zone of inhibition. In conclusion, out of five pigments producing fungi, Aspergillus terreus S10 and Talaromyces atroroseus produced maximum pigment and highest percentage absorbance under liquid state fermentation conditions. Potential applications in the textile and leather industries have been discovered as a result of this research.